Improving growth, productivity and energetics of mungbean (Vigna radiata) through soil and foliar application of zinc - KAUR, LAKHWINDER; SHARMA, RAJNI (The Indian Journal of Agricultural Sciences, 2025)
The present experiment was conducted during rainy (kharif) seasons of 2021 and 2022 at Punjab Agricultural University, Ludhiana, Punjab to evaluate the effect of zinc sulphate (ZnSO4.7H2O) on growth, yield and productivity of mungbean [Vigna radiata (L.) Wilczek] under semi-arid and subtropical conditions. The experiment was laid out in a randomized complete block design (RCBD) with four replications. Results revealed that soil applied ZnSO4 at 20 kg/ha along with foliar spray of Zn (0.5%) at both flower initiation and pod formation phases attributed significant increase in growth and yield attributes of mungbean and was statistically similar with ZnSO4 application to soil at 20 kg/ha along with 0.5% foliar spray at initiation of flowering alone. The per cent increase in yield was 14.6% and 15.0% with this treatment over control for two years of the study, respectively. The maximum energy output (14448.6 and 14658 MJ/ha) and energy productivity (204.3 and 207.3 g/MJ) was observed with soil Zn application at 20 kg/ ha + 0.5% foliar spray at initiation of flowering and pod formation stages during 2021 and 2022, respectively. Thus, zinc sulphate application has greater effect on augmenting growth, productivity and energetics of mungbean.